Ultraviolet light resistant screen printing ink, preparation method and application thereof

CN122686176APending Publication Date: 2026-09-04YIYANG NASHENG MATERIALS TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610877513.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-17
Publication Date
2026-09-04

AI Technical Summary

Technical Problem

[0004]然而,将常规PEDOT:PSS材料直接应用于车载环境仍面临严峻挑战

Benefits of technology

(1)本发明在对高电导率PEDOT:PSS原液进行后添加改性时,引入了由羟基乙叉二膦酸(HEDP)与单宁酸构成的专用复配体系。HEDP分子中的多个膦酸基团能够与PSS链上的磺酸基团形成强烈的螯合作用,犹如“分子锚”一般,将PEDOT与PSS的结合结构固定得更加牢固。HEDP构建的稳固物理框架,确保了单宁酸能够稳定地存在于PEDOT:PSS体系中,并更充分地接触和清除自由基。同时,单宁酸通过氢键等作用与PSS/HEDP网络进一步交联,也增强了整体的结构致密性。二者共同构建了一个兼具物理稳定性(HEDP提供)与化学稳定性(单宁酸提供)的复合防护网络。该复配体系能通过螯合与抗氧化的协同作用,有效淬灭紫外光引发的自由基并抑制光氧化链式反应,从而显著提升油墨成膜后的耐紫外辐照性能。基于此创新配方,本发明油墨在保持高导电性、高透光率和优异附着力的同时,更具备了抗氧化性及卓越的耐UV性能,完美契合丝网印刷工艺与车载环境的苛刻要求,为新能源汽车提供了高性能、高可靠性及低成本的触控解决方案。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application discloses a kind of ultraviolet light irradiation resistant silk screen printing ink, by weight parts, the ultraviolet light irradiation resistant silk screen printing ink includes PEDOT:PSS water dispersion 26.0-55.0 parts, conductive reinforcing agent 30.0-62.0 parts, coupling agent 0.4-1 part, thickening agent 1.0-2.0 parts, adhesive 2.0-6.0 parts, auxiliary 0.4-3.0 parts, curing agent 0-2.0 parts, first UV inhibitor 0.3-1.5 parts, the PEDOT:PSS water dispersion includes PEDOT:PSS and second UV inhibitor, the first UV inhibitor and the second UV inhibitor jointly constitute UV inhibitor compound system, the first UV inhibitor is tannin, the second UV inhibitor is hydroxyethylidene diphosphonic acid, the weight parts of UV inhibitor compound system is 0.5-2.5 parts.The light transmittance and UV performance of silk screen printing ink film can be significantly improved, and the square resistance is reduced by modifying PEDOT:PSS water dispersion and optimizing overall formulation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of conductive polymer composite materials technology, specifically relating to a UV-resistant screen printing ink based on PEDOT:PSS, its preparation method, and its application. Background Technology

[0002] With the rapid development of the new energy vehicle industry and the popularization of intelligent cockpits, in-vehicle human-machine interfaces are evolving towards larger sizes, curved surfaces, and integration. This places higher demands on transparent electrode materials used for touch sensors: they not only need excellent conductivity and optical transparency, but also must possess outstanding mechanical flexibility, environmental stability (especially resistance to ultraviolet aging), and processing technology suitable for printing on complex curved surfaces.

[0003] While traditional indium tin oxide (ITO) thin films are widely used, their inherent brittleness, high-cost vacuum fabrication process, and incompatibility with curved surfaces make them unsuitable for the design requirements of next-generation smart cockpits. Against this backdrop, intrinsically conductive polymers, particularly PEDOT:PSS, have emerged as ideal alternatives due to their unique advantages. PEDOT itself possesses high electrical conductivity and excellent chemical stability, while the water-soluble polyelectrolyte PSS acts as a colloidal stabilizer and counterion agent, enabling PEDOT to form a stable, deep blue, water-based dispersion through electrostatic interactions. The resulting PEDOT:PSS conductive ink combines high transparency, excellent flexibility, and environmental friendliness.

[0004] However, directly applying conventional PEDOT:PSS materials to the automotive environment still faces significant challenges. Vehicles are constantly exposed to the outdoors, and their interior touch panels are subjected to intense sunlight, especially ultraviolet radiation, which triggers photodegradation of most organic polymers, leading to decreased conductivity and yellowing, thus affecting product lifespan and reliability. Conventional UV stabilizers often struggle to strike a balance between effective protection and maintaining the basic properties of the ink, making it difficult to simultaneously achieve good light transmittance, UV performance, and sheet resistance. Summary of the Invention

[0005] In order to overcome the problems in the prior art, the technical solution proposed in this invention, through modification of PEDOT:PSS aqueous dispersion and overall formulation optimization, can significantly improve the light transmittance and UV performance of screen printing ink film and reduce sheet resistance.

[0006] To solve the above-mentioned technical problems, the present invention proposes the following technical solution: a UV-resistant screen printing ink, comprising, by weight, 26.0-55.0 parts of PEDOT:PSS aqueous dispersion, 30.0-62.0 parts of conductive enhancer, 0.4-1 parts of coupling agent, 1.0-2.0 parts of thickener, 2.0-6.0 parts of binder, 0.4-3.0 parts of additive, 0-2.0 parts of curing agent, and 0.3-1.5 parts of a first UV inhibitor. The PEDOT:PSS aqueous dispersion comprises PEDOT:PSS and a second UV inhibitor. The first UV inhibitor and the second UV inhibitor together constitute a UV inhibitor compound system. The first UV inhibitor is tannic acid, and the second UV inhibitor is hydroxyethylidene diphosphonic acid. The weight of the UV inhibitor compound system is 0.5-2.5 parts.

[0007] Preferably, the mass ratio of the first UV inhibitor to the second UV inhibitor is 1:1 to 1:2.

[0008] The conductivity enhancer is at least one selected from dimethyl sulfoxide, ethylene glycol, sulfolane, diethylene glycol, 1,2-pentanediol, or 1,2-propanediol. The conductivity enhancer is a high-boiling-point polar solvent, more preferably dimethyl sulfoxide (DMSO).

[0009] The coupling agent is at least one selected from 3-glycidoxypropyltrialkoxysilane, 3-aminopropyltriethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-methacryloyloxypropyltrimethoxysilane, vinyltrimethoxysilane, or octyltriethoxysilane. In this invention, the coupling agent enhances the interaction between the components within the material, improves the overall performance and stability of the material, helps improve the adhesion of PEDOT:PSS ink, and enhances the water resistance of the film. More preferably, the coupling agent is 3-glycidoxypropyltrialkoxysilane, specifically KH560 coupling agent.

[0010] The thickener is at least one selected from modified cellulose, polyurea, polyacrylate, or associative polyurethane thickener. More preferably, the thickener is a polyurea thickener, specifically BYK-7420 thickener.

[0011] The adhesive is at least one of acrylic resin, polyurethane resin, polyester resin or polyvinyl alcohol.

[0012] Preferably, the adhesive is a mixture of polyurethane resin and polyvinyl alcohol. More preferably, the mass of polyurethane resin is greater than that of polyvinyl alcohol, and the improvement effect is particularly significant when the mass ratio is 3:1. Specifically, polyvinyl alcohol can be selected as PVA1799 or PVA105, with a degree of hydrolysis of 85%-99%. This invention has found that using a combination of polyurethane resin and PVA adhesive can significantly improve the UV resistance of the PEDOT:PSS conductive layer. The mechanism of action lies in the fact that the inherent conjugated units, such as the benzene ring, in the polyurethane resin molecular structure can effectively absorb and dissipate ultraviolet light energy, playing an essential "shielding" effect. Simultaneously, the abundant hydroxyl groups on the PVA molecular chain form a dense hydrogen bond network with the sulfonic acid groups in PEDOT:PSS and the polar groups in polyurethane, thereby stabilizing the overall composite structure and inhibiting chain breakage and phase separation caused by ultraviolet irradiation. Furthermore, the hydroxyl groups of PVA themselves can act as sacrificial groups, preferentially reacting with ultraviolet-excited active free radicals, thus delaying the attack and oxidative degradation of the PEDOT conjugated structure by active free radicals. Through the synergistic effects of physical shielding, structural stabilization, and chemical protection, polyurethane and PVA jointly construct a robust ultraviolet protection system, ultimately achieving stable electrical properties of the PEDOT:PSS composite material under long-term ultraviolet aging conditions.

[0013] The curing agent is at least one selected from isocyanate compounds, aziridine compounds, carbodiimide compounds, oxazoline compounds, epoxy resin compounds, or amino resin compounds. Preferably, the curing agent is 0.5-2.0 parts by weight. More preferably, the curing agent is a water-based blocked isocyanate curing agent, specifically a water-based blocked isocyanate curing agent commercially available from LANXESS.

[0014] The additives include at least one of a leveling agent, a surface wetting agent, a defoamer, and a pH adjuster. The leveling agent is at least one of a polyether-modified polysiloxane, an acrylate polymer, or a fluorocarbon polymer. The surface wetting agent is at least one of an ethynyl alcohol surfactant, a fluorinated surfactant, or an anionic surfactant. The defoamer is at least one of a mineral oil, a polyether, or an organosilicon defoamer. The pH adjuster is at least one of an organic amine, an inorganic alkali, or an organic acid, used to adjust the pH of the screen printing ink to 2.0-7.0.

[0015] Furthermore, the leveling agent is a polyether-modified polysiloxane (polyether siloxane copolymer) type silicone leveling agent, specifically a commercially available product under the trade name TEGO, such as TEGO Glide 450; the surface wetting agent is an acetylenol surfactant or anionic surfactant, specifically Surfynol 465 or Surfynol 61, and the anionic surfactant is at least one of alkylbenzene sulfonate, alkane sulfonate, sulfosuccinate, phosphate ester or alkyl ether carboxylate; the defoamer is a silicone defoamer, specifically TEGO 810; and the pH adjuster is triethanolamine, ammonia, dimethylethanolamine or imidazole.

[0016] Preferably, the content of PEDOT:PSS in the PEDOT:PSS aqueous dispersion is 0.8wt-3wt%.

[0017] The preparation method of the above-mentioned UV-resistant screen printing ink includes the following steps:

[0018] S1. Mix the PEDOT:PSS aqueous dispersion with the coupling agent to obtain the first mixture; S2. Add a portion of the conductivity enhancer to the first mixture, and after mixing, obtain the second mixture; S3. Add the first UV inhibitor and the auxiliary agent to the second mixture, and mix to obtain the third mixture; S4. Add the adhesive to the third mixture and mix to obtain the fourth mixture; S5. Add the remaining conductive enhancer used as a slow-drying solvent to the fourth mixture, then add the thickener, and finally add the curing agent. After mixing, filter to remove impurities.

[0019] In step S1, the preparation method of the PEDOT:PSS aqueous dispersion includes the following steps: (1) Preparation of oxidant solution: In the reaction vessel, add EDOT monomer, PSSNa, deionized water and hydroxyethylidene diphosphonic acid. The effective solid content ratio of EDOT and PSSNa is between 2.5 and 4.5:1. Mix by stirring and undergo shear emulsification to form a homogeneous aqueous dispersion. In another reaction vessel, prepare an aqueous solution of composite oxidant composed of sodium persulfate and ferric sulfate. (2) Polymerization reaction: Under nitrogen protection, temperature of 10-20℃ and oxygen content of less than 30ppb, the aqueous solution of the composite oxidant is added to the homogeneous aqueous dispersion. The molar ratio of sodium persulfate to EDOT monomer is 1.17-1.2:1, and the molar ratio of ferric sulfate to EDOT monomer is 0.005-0.01:1. The stirring speed is controlled at 800rpm-1200rpm, and the polymerization reaction is carried out for 12-36h. (3) Post-processing: After the polymerization reaction is completed, ion exchange resin treatment and high pressure homogenization treatment are carried out in sequence. The pressure range of high pressure homogenization is 800-1500 bar. Then, the mixture is concentrated by molecular sieve or low temperature evaporation. The temperature of low temperature evaporation is 45-55℃ to obtain PEDOT:PSS polymer aqueous dispersion.

[0020] Preferably, the conductive reinforcing agent added in step S2 accounts for 25-35% of the total conductive reinforcing agent by mass, and the remaining conductive reinforcing agent is added in step S5.

[0021] The present invention also provides the application of the above-mentioned UV-resistant screen printing ink in vehicle control panels, luminous logos, capacitive touch switches for home appliances and furniture, cold light sheets, 3D luminous masks, ambient lights, luminous letters, electrochromic devices, and transparent electrodes.

[0022] Compared with the prior art, the beneficial effects of the present invention are as follows: (1) In the post-modification of the high-conductivity PEDOT:PSS stock solution, this invention introduces a special compound system composed of hydroxyethylidene diphosphonic acid (HEDP) and tannic acid. Multiple phosphonic acid groups in the HEDP molecule can form a strong chelating effect with the sulfonic acid groups on the PSS chain, acting like a "molecular anchor" to firmly fix the bond between PEDOT and PSS. The robust physical framework constructed by HEDP ensures that tannic acid can exist stably in the PEDOT:PSS system and more fully contact and scavenge free radicals. Simultaneously, tannic acid further crosslinks with the PSS / HEDP network through hydrogen bonding and other interactions, enhancing the overall structural density. Together, they construct a composite protective network that combines physical stability (provided by HEDP) and chemical stability (provided by tannic acid). This compound system can effectively quench UV-induced free radicals and inhibit photo-oxidation chain reactions through the synergistic effect of chelation and antioxidation, thereby significantly improving the UV radiation resistance of the ink film. Based on this innovative formula, the ink of this invention maintains high conductivity, high light transmittance and excellent adhesion, while also possessing antioxidant properties and excellent UV resistance, perfectly meeting the stringent requirements of screen printing processes and automotive environments, and providing a high-performance, high-reliability and low-cost touch solution for new energy vehicles.

[0023] (2) The aqueous dispersion based on PEDOT:PSS conductive polymer prepared in this invention is insensitive to water and can maintain stable performance under harsh conditions such as temperature, humidity and chemical corrosion. Its conductivity is higher, which makes its film transmittance higher and the acidity of the system is weaker, thus avoiding the corrosion of the substrate by the prepared ink. After working together with coupling agent and conductive enhancer, it further enhances the stability, adhesion and water resistance of ink, enabling it to adapt to complex and changeable use environment. Furthermore, after working together with the subsequently added first UV inhibitor, thickener and curing agent, it significantly enhances UV performance and extends service life, and improves adhesion and water resistance. Detailed Implementation

[0024] The present invention will be described in detail below through embodiments, but the scope of protection of the present invention is not limited to the following description. Unless otherwise defined, all technical terms used herein have the same meaning as commonly understood by those skilled in the art. The technical terms used herein are for the purpose of describing particular embodiments only and are not intended to limit the scope of protection of the present invention.

[0025] Unless otherwise specified, all raw materials, reagents, instruments and equipment used in this invention can be purchased from the market or prepared by existing methods.

[0026] Preparation Example 1: The PEDOT:PSS polymer aqueous dispersion was prepared by the following steps: (1) Premixing and preparation of oxidant solution: In the reaction vessel, add 36 ml of PSS (polystyrene sulfonic acid) and 0.5 ml of EDOT monomer (3,4-ethylenedioxythiophene) to 700 ml of deionized water, and then add 1.5 g of hydroxyethylidene diphosphonic acid. Stir at room temperature for 30-50 min. After stirring into a milky white liquid, emulsify it by high-speed shearing to form a homogeneous aqueous dispersion. In another independent container, prepare an aqueous solution of composite oxidant consisting of 10 g of sodium persulfate and 0.6 g of ferric sulfate in 100 ml of deionized water. (2) Polymerization reaction: Under nitrogen protection, temperature of 10-20℃ and oxygen content of less than 30 ppb, the aqueous solution of the composite oxidant is slowly added to the aqueous dispersion, and the stirring speed is controlled at 1000 rpm for 20-24 h of polymerization reaction. (3) Post-treatment: After the reaction was completed, 300 ml of strong acid cation exchanger (Lewatit S100, Lanxess AG) and 600 ml of weak acid anion exchanger (Lewatit MP62, Lanxess AG) were added to remove inorganic salts. The solution was stirred for 10 h and the ion exchanger was filtered out through a filter screen. Then, the solution was homogenized 10 times at 1000 bar using a high-pressure homogenizer. The resulting original solution was then evaporated at 50 °C to remove 40% of the water. The solid content of the original solution was about 3.0%. The solution was homogenized 5 times again at 1000 bar using a high-pressure homogenizer to obtain the high solid content original solution ①.

[0027] Preparation Example 2: The preparation method of the high solids content stock solution ② differs from that of preparation example 1 in that: during the post-processing, instead of evaporating 40% of the water from the obtained stock solution by evaporation at 50°C, 40% of the water is removed by molecular sieve (particle size (mesh number) 3A-4A).

[0028] Preparation Example 3: The preparation method of the high solids content stock solution ③ differs from that of preparation example 1 in that the organic acid hydroxyethylidene diphosphonic acid was not added.

[0029] Preparation Example 4: The preparation method of the high solids content stock solution ④ differs from that of preparation example 1 in that 3g of organic acid hydroxyethylidene diphosphonic acid was added.

[0030] Examples 1-8 and Comparative Examples 1-4: Using the PEDOT:PSS polymer aqueous dispersion (i.e., high solids content stock solution) prepared in the preparation example as raw material, the PEDOT:PSS polymer aqueous dispersion was stirred evenly, then a coupling agent was added and stirred evenly, followed by 30 wt% of a conductive enhancer and stirred evenly, then tannic acid, leveling agent, surface wetting agent, defoamer, and pH adjuster were added and stirred evenly, then a binder was added and stirred evenly, then stirred evenly again, then the remaining 70 wt% of the conductive enhancer was added and stirred evenly, then a thickener was added and stirred evenly again, finally a curing agent was added and stirred evenly, and impurities were removed by vacuum filtration to obtain the PEDOT:PSS screen printing ink. The formulation specific gravity and performance data of different PEDOT:PSS screen printing inks in the examples and comparative examples are shown in Table 1 below. If the weight part is 0 parts, it means that the component was not added based on the above process steps.

[0031] Screen printing with screen printing inks: (1) Stir the high thermal stability PEDOT:PSS screen printing ink evenly; (2) Pour an appropriate amount of ink onto one end of the screen (non-pattern area). First, use a back-inking knife to evenly spread the ink across the entire pattern area of ​​the screen. Perform 1-2 test prints to check the clarity, integrity, and positional accuracy of the pattern. Then proceed with screen printing, maintaining uniform speed, stable pressure, and complete stroke during the squeegee process. (3) Baking: Place the printed material on a hot table at 130℃ and cure for 20-30 minutes.

[0032] Relevant performance testing methods: (1) Initial sheet resistance: The initial sheet resistance range of the thin film was measured using a four-probe sheet resistance meter; (2) Transmittance (T) and Haze (H) Tests: The transmittance of the thin film was tested using an LH-206 optical transmittance meter (Shenzhen Lianhuicheng Technology Co., Ltd.). This instrument adopts a parallel optical path design and has built-in ultraviolet (365nm), visible (380-760nm), and infrared (940nm) three-band light sources. The transmittance percentage is calculated by measuring the incident light intensity and the light intensity after passing through the sample. The measurement accuracy is ≤±2%. The haze test was conducted using a YH series haze meter.

[0033] (3) UV aging resistance rate: Place the screen-printed film on the sample rack of the test chamber (AV90C-240V 365nm-120W), ensuring that the test surface is uniformly exposed to UV light. Start the UV aging test chamber and run the set test cycle (each cycle is 8 minutes, and the energy of a single cycle is approximately 35000mJ / cm). 2 After each cycle, the thin film was removed and the sheet resistance range was tested using a four-probe sheet resistance meter. After ten cycles, the rate of change was calculated and compared.

[0034] (4) Cross-cut adhesion test Cleaning: Use a lint-free cloth to clean the test area, ensuring the surface is free of oil, dust, and fingerprints; Instrument Inspection: Inspect the cross-cut test blade to ensure all edges are sharp, undamaged, and securely installed. Select a blade spacing appropriate for the coating thickness (e.g., 1mm, 2mm). Positioning Cut: Place the template on a hard, flat surface. Hold the cross-cut cutter firmly and perpendicular to the template surface. First Cut: With even and appropriate pressure, push the cutter holder smoothly in one go to cut the first set of parallel lines on the coating. When cutting, ensure that the blade penetrates the coating to the substrate. Second Cut: Rotate the cross-cut cutter 90° to cut another set of perpendicular parallel lines on the first set of cuts, forming a grid pattern. Clean up debris: Use a soft-bristled brush or ear syringe to gently sweep along the diagonal of the grid 5-6 times to remove loose debris generated during cutting; Tape Test: Firmly adhere standard tape (e.g., 3M #610) to the cut grid area, pressing firmly with your fingers or an eraser to ensure full contact between the tape and the coating. After 10 seconds, pinch one end of the tape and peel it off at a 180° angle within 0.5-1.0 seconds. Result Comparison: Immediately observe the coating peeling in the grid area under sufficient light using a magnifying glass.

[0035] (5) Water resistance test Preparation of wet cloth: Soak pure cotton cloth thoroughly with distilled water, then wring it out until no water drips (moisture content is about 80%). Fix the sample and cloth: Fix the test film sample, wrap the wet cloth around the instrument friction head and press it with the specified weight (2kg). Setting parameters: Load: 2kg, Stroke: 100mm, Speed: 30-60 cycles / min, Number of cycles: as required: stop when the film peels off, perform test: start the instrument and wipe the coating surface repeatedly with a wet cloth under the set parameters; Results evaluation: After the test, immediately use a dry cloth to gently absorb the excess moisture on the sample surface. Under standard light, observe whether there are any phenomena such as wrinkling, bubbling, whitening, fading, or peeling in the wiped area, and compare it with the unwiped area.

[0036] Table 1. Test results of components (parts by weight) and performance data in Examples 1-8 and Comparative Examples 1-4.

[0037] By comparing Example 1 with Comparative Example 1 and Example 2 with Comparative Example 2, it can be seen that the weather resistance of the screen printing coating is significantly improved after introducing the first UV inhibitor described in this invention into the ink formulation. UV aging test data shows that this additive effectively inhibits the degradation of the conductive network caused by photo-oxidation, reducing the sheet resistance change rate of the test area by approximately 50%.

[0038] Comparing Examples 1 and 2, it is evident that the ink formulated using high-solids-content concentrate ② outperforms the system using high-solids-content concentrate ① in both core optical performance and UV resistance. Based on its superior transmittance and lower haze, the ink formulated using high-solids-content concentrate ② delivers a more transparent visual effect and lower light scattering loss. This characteristic makes it suitable not only for general decoration but also for printing on precision electronic components such as high-transmittance panels, optical lenses, and high-end displays. Furthermore, the method of achieving high-solids-content concentrate improves UV resistance to a certain extent. This indicates that the implementation path of the concentrate itself has a positive impact on the overall performance of the final coating.

[0039] By comparing Example 1 with Comparative Examples 3 and 4, it can be seen that, compared with high-solids-content stock solution ③, the ink using high-solids-content stock solution ① (i.e., a compound system containing hydroxyethylidene diphosphonic acid and tannic acid) achieves an order-of-magnitude improvement in its UV resistance. This result demonstrates that this organic acid compound combination can significantly enhance the thermal stability and UV resistance of PEDOT:PSS conductive films.

[0040] Comparing the test results of Example 1 and Example 3, it can be seen that the ink prepared using high solids content solution ④ has slightly improved thermal stability and UV resistance compared to the ink prepared using high solids content solution ①; the relevant properties of both inks are within the applicable range, and their overall performance is excellent.

[0041] By comparing Examples 2 and 4, it can be seen that, in terms of resin system selection, the formulation using a combination of polyurethane and polyvinyl alcohol exhibits significantly better UV resistance than the polyester resin system, indicating that the chemical structure of the polymer binder has a significant impact on the light stability of the coating.

[0042] Comparing Examples 4 and 5, the introduction of a curing agent into the product formulation effectively promoted the cross-linking reaction of the ink resin, forming a denser three-dimensional network structure. This structural optimization significantly enhanced the adhesion between the coating and the substrate and created an excellent water penetration barrier. Test results show that this optimization substantially improved the reliability and service life of the product under harsh environments.

[0043] By comparing Examples 6 and 7 with Examples 1 and 3, it was found that when the mass ratio of tannic acid to hydroxyethylidene diphosphonic acid in the formulation was controlled, the coating’s UV resistance was better than that of the ratio outside this range.

[0044] Compared with other examples and comparative examples, Example 8 has lower UV resistance than the other examples. This is because the amount of PEDOT:PSS has a significant impact on UV resistance, and the higher the amount, the better the performance within the scope of the study. Meanwhile, Example 8 has better performance than the comparative examples because its formulation contains a combination of tannic acid and hydroxyethylidene diphosphonic acid, which can still maintain better UV resistance. This solution is particularly suitable for applications that require high transparency.

[0045] PEDOT: Whether or not hydroxyethylidene diphosphonic acid (HEDTA), a second UV inhibitor, is added during the synthesis of PSS stock solution is a key variable determining the UV resistance of inks. Products containing and without this additive show significant differences in their resistance to UV aging. HEDTA possesses strong metal ion chelating and free radical scavenging capabilities, inhibiting photo-induced degradation reactions and thus significantly improving the UV resistance of inks. If this component is missing during synthesis, the ink's performance degradation under light exposure will be accelerated.

[0046] Currently, the two concentration methods used are low-temperature evaporation concentration and molecular sieve concentration. Their essential difference lies in the heating temperature and duration of the material. Molecular sieve technology, due to its shorter heating time and lower heat load, can better preserve the original properties of the original solution. PEDOT: PSS, as a conductive polymer system, is heat-sensitive. Prolonged or high-temperature heating can lead to polymer chain aggregation, structural collapse, or deterioration of conductivity.

[0047] Low-temperature evaporation concentration: This method evaporates water through heating, but the material is heated for a long time, and the high-temperature environment can easily cause thermal damage to the polymer chains. Molecular sieve concentration: This method utilizes molecular sieves to selectively adsorb water, usually carried out at room temperature or lower, and the dehydration speed is fast. Due to the low heating temperature and short time, thermal degradation is effectively avoided, and the integrity of the polymer chains and the initial conductive network structure of the original solution are preserved to the greatest extent, thus protecting the performance of the original solution.

[0048] The first UV inhibitor can synergistically work with the hydroxyethylidene diphosphonic acid already present in the system to significantly improve the stability of the cured coating under ultraviolet irradiation, effectively suppress the conductivity decay and yellowing caused by photoaging, thereby bringing a longer service life to automotive touch products.

[0049] The introduction of polymer binders can not only effectively improve the leveling properties of inks and enhance their adhesion to flexible substrates such as PET, but also improve the mechanical toughness and scratch resistance of the cured film. Furthermore, the film-forming density and UV shielding properties of the selected resins themselves can synergistically work with the UV inhibitors in the system, providing effective support for the overall UV aging resistance of the inks.

[0050] By introducing the aforementioned curing agent and performing thermosetting at 120~150℃, the ink can form a cross-linked network on the PET substrate. Testing shows that its adhesion reaches a 5B grade in the cross-cut adhesion test, and it withstands over 20 water wiping cycles (with a 2kg weight), fully meeting the stringent reliability requirements of the automotive environment.

Claims

1. A screen printing ink resistant to ultraviolet light, characterized in that, By weight, the UV-resistant screen printing ink comprises 26.0-55.0 parts of PEDOT:PSS aqueous dispersion, 30.0-62.0 parts of conductive enhancer, 0.4-1 parts of coupling agent, 1.0-2.0 parts of thickener, 2.0-6.0 parts of binder, 0.4-3.0 parts of additives, 0-2.0 parts of curing agent, and 0.3-1.5 parts of first UV inhibitor. The PEDOT:PSS aqueous dispersion comprises PEDOT:PSS and second UV inhibitor. The first UV inhibitor and the second UV inhibitor together form a UV inhibitor compound system. The first UV inhibitor is tannic acid, and the second UV inhibitor is hydroxyethylidene diphosphonic acid. The weight of the UV inhibitor compound system is 0.5-2.5 parts.

2. The UV-resistant screen printing ink according to claim 1, characterized in that, The mass ratio of the first UV inhibitor to the second UV inhibitor is 1:1 to 1:

2.

3. The UV-resistant screen printing ink according to claim 1, characterized in that, The conductivity enhancer is at least one of dimethyl sulfoxide, ethylene glycol, sulfolane, diethylene glycol, 1,2-pentanediol, or 1,2-propanediol.

4. The UV-resistant screen printing ink according to claim 1, characterized in that, The coupling agent is at least one of 3-glycidoxypropyltrialkoxysilane, 3-aminopropyltriethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-methacryloyloxypropyltrimethoxysilane, vinyltrimethoxysilane, or octyltriethoxysilane.

5. The UV-resistant screen printing ink according to claim 1, characterized in that, The thickener is at least one of modified cellulose, polyacrylate, or associative polyurethane thickener.

6. The UV-resistant screen printing ink according to claim 1, characterized in that, The adhesive is at least one of acrylic resin, polyurethane resin, polyester resin or polyvinyl alcohol.

7. The UV-resistant screen printing ink according to claim 6, characterized in that, The adhesive is a mixture of polyurethane resin and polyvinyl alcohol.

8. The UV-resistant screen printing ink according to claim 1, characterized in that, The curing agent is at least one of isocyanate compounds, aziridine compounds, carbodiimide compounds, oxazoline compounds, epoxy resin compounds, or amino resin compounds.

9. The UV-resistant screen printing ink according to claim 1, characterized in that, The additives include at least one of a leveling agent, a surface wetting agent, a defoamer, and a pH adjuster. The leveling agent is at least one of a polyether-modified polysiloxane, an acrylate polymer, or a fluorocarbon polymer. The surface wetting agent is at least one of an acetylenol surfactant, a fluorinated surfactant, or an anionic surfactant. The defoamer is at least one of a mineral oil, a polyether, or an organosilicon defoamer. The pH adjuster is at least one of an organic amine, an inorganic alkali, or an organic acid. The additives are used to adjust the pH of the screen printing ink to 2.0-7.

0.

10. The UV-resistant screen printing ink according to any one of claims 1-9, characterized in that, The PEDOT:PSS content in the PEDOT:PSS aqueous dispersion is 0.8wt-3wt%.

11. The method for preparing UV-resistant screen printing ink according to any one of claims 1-10, characterized in that, Includes the following steps: S1. Mix the PEDOT:PSS aqueous dispersion with the coupling agent to obtain the first mixture; S2. Add a portion of the conductivity enhancer to the first mixture, and after mixing, obtain the second mixture; S3. Add the first UV inhibitor and the auxiliary agent to the second mixture, and mix to obtain the third mixture; S4. Add the adhesive to the third mixture and mix to obtain the fourth mixture; S5. Add the remaining conductive enhancer used as a slow-drying solvent to the fourth mixture, then add the thickener, and finally add the curing agent. After mixing, filter to remove impurities.

12. The method for preparing UV-resistant screen printing ink according to claim 11, characterized in that, In step S1, the preparation method of the PEDOT:PSS aqueous dispersion includes the following steps: (1) Preparation of oxidant solution: In the reaction vessel, add EDOT monomer, PSSNa, deionized water and hydroxyethylidene diphosphonic acid. The effective solid content ratio of EDOT and PSSNa is between 2.5 and 4.5:

1. Mix by stirring and undergo shear emulsification to form a homogeneous aqueous dispersion. In another reaction vessel, prepare an aqueous solution of composite oxidant composed of sodium persulfate and ferric sulfate. (2) Polymerization reaction: Under nitrogen protection, temperature of 10-20℃ and oxygen content of less than 30ppb, the aqueous solution of the composite oxidant is added to the homogeneous aqueous dispersion. The molar ratio of sodium persulfate to EDOT monomer is 1.17-1.2:1, and the molar ratio of ferric sulfate to EDOT monomer is 0.005-0.01:

1. The stirring speed is controlled at 800rpm-1200rpm, and the polymerization reaction is carried out for 12-36h. (3) Post-processing: After the polymerization reaction is completed, ion exchange resin treatment and high pressure homogenization treatment are carried out in sequence. The pressure range of high pressure homogenization is 800-1500 bar. Then, the mixture is concentrated by molecular sieve or low temperature evaporation. The temperature of the low temperature evaporation is 45-55℃ to obtain PEDOT:PSS aqueous dispersion.

13. The method for preparing UV-resistant screen printing ink according to claim 11, characterized in that, The conductive reinforcing agent added in step S2 accounts for 25-35% of the total conductive reinforcing agent by mass, and the remaining conductive reinforcing agent is added in step S5.

14. The application of UV-resistant screen printing ink as described in any one of claims 1-10 or prepared by any one of claims 11-13 in vehicle control panels, luminous logos, capacitive touch switches for home appliances and furniture, cold light sheets, 3D luminous masks, ambient lights, luminous letters, electrochromic devices, and transparent electrodes.